PENGARUH KONSENTRASI DAN FREKUENSI PEMBERIAN PUPUK METALIK TERHADAP PERTUMBUHAN TANAMAN LADA PERDU (Piper nigrum) DI PEMBIBIT AN - Bambang S. Purwoko; Yeni Yudhiani; Muhammad Syakir (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
The objective of the experiment was to determine the best concentration and frequency of application of micronutrients (Metalik) to increase pepper plant growth in the nursery. Metalik was used as it contained several micronutrients. Thirteen treatments were arranged as follows: untreated plants as control and twelve other treatments were combinations of concentration (0.3, 0.6, 0.9, 1.2 ml Metalik/l water denoted as KO.3, KO.6, KO.9, and K1.2 respectively) and application frequency (once a week, once every two weeks, and once every four weeks denoted as Fl, F2, and F41respectively). The twelve treatments were: KO.3Fl, KO.3F2, KO.3F4, KO.6Fl, KO.6F2, KO.6F4, KO.9F1, KO.9F2, KO.9F4, Kl.2F1, Kl.2F2, and Kl.2F4. Plants used in the experiment originated: from secondary branch cuttings of Lampung Daun Lebar cultivar. A randomized complete blocked design was used. Experiment consisted of three replicates. Result of the experiment showed that foliar application of Metalik increased growth of pepper plants in the nursery. The best treatment was concentration of 0.3 ml Metalik/l water and application frequency of once every four weeks.